Body mass index and dental caries in native Peruvian communities - Christian Renzo Aquino Canchari; Diego Andre Crisol-Deza; Joselyn Linda Zurita-Borja (Universidade Estadual de Campinas, 2020)
Oral disorders and eating disorders affect everyone, however,these will be more frequent in vulnerable populations suchas native communities. Aim: Determining the body massindex and the prevalence of dental caries and its clinicalconsequences in native Peruvian communities. Methods:Observational, correlational, cross-sectional study. The sampleconsisted of 169 adults from the native communities selectedfor convenience, meeting inclusion and exclusion criteria.Nutritional status was evaluated through the body mass index,to quantify the experience of dental caries, the DMTF index wasused, the severity was quantified by the significance index ofdental caries, and its clinical consequences when not beingtreated by the PUFA index. The evaluation was carried out innatural light by calibrated observers. The data were analyzedin the STATA v 14 program using frequency distribution tablesand figures, to determine the association, the Pearson'scorrelation coefficient was used. Results: The majority ofresidents had an adequate weight for their height 71 (41.01%),followed by low weight 64 (37.87%), overweight 29 (17.16%)and obesity 5 (2.96% ). The prevalence of dental caries was100% (DMTF = 13.23; SIC = 19.01), of which 68.04% had clinicalconsequences, no association was found between: BMI andDMTF (p = 0.557) BMI and PUFA-index (0.485). Conclusions:No association was found between the body mass index anddental caries and its clinical consequences.